Age and career resilience through the lens of life course theory: Examining individual mechanisms and macro-level context across 28 countries - Goštautaitė, B.; Kim, N.; Steindórsdóttir, B. D.; Parry, E.; Dello Russo, S.; Andresen, M.; Buranapin, S.; Bosak, J.; Cerdin, J.-L.; Chudzikowski, K.; Cotton, R.; Dickmann, M.; et al. (Human Resource Management Journal, 2025)
Career resilience is critical to the world's aging workforce, aiding older workers in adapting to the ever-evolving nature of work. While ageist stereotypes often depict older workers as less resilient when faced with workplace changes, existing research studies offer conflicting evidence on whether older age hinders or improves career resilience. In response to this conflicting evidence, the present study employs multi-level data from 6772 employees in 28 countries to examine the age-career resilience relationships and underlying mechanisms, hence advancing our understanding of career resilience across the life course. By integrating macro-contextual factors such as the unemployment rate and the culture of education with individual-level mechanisms such as positive career meaning and career optimism, we provide a comprehensive model explaining how career resilience varies across age groups. Grounded in life course theory, our findings resolve prior inconsistencies in resilience research, contribute to bridging the micro-macro gap in HRM literature, and challenge existing age-based stereotypes.